Tremor Indicators In The Operational And Psychosensory Rest - Lobasyuk, B. A.; Akіmova, L. N.; Bodelan, М. I.; Aymedov, К. V. (Psychiatry, Neurology and Medical Psychology, 2016)
We have investigated postural tremor using the original method developed by the authors using coal-resistive sensor in right-handers. Identified various indicators in terms of operative rest (eyes open) and under psychosensory resting (eyes closed). Tremorogrammy asymmetry index expresses the positive values in the operational conditions of peace, to witwas dominated by the left hand of the amplitude, and in conditions of peace psychosensory asymmetry indices decreased. It is expected that the physiological tremor of the hands of the control mechanisms in terms of operational and psychosensory rest are not identical.